DEVELOPMENT OF TRADE AND COMMERCE IN GOALPARA DURING COLONIAL PERIOD - Boroowa, Diganta Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The paper tries to study the development of Trade and commerce during colonial period in Goalpara. Before the East India Company’s ascendency Goalpara was under the control of the Mughal Empire. Goalpara was the most important trade point of Bengal and Assam. Goalpara has acted as the gateway to Assam for centuries. The various kinds of trades were known in Goalpara since early times. The early nineteenth century was the period of transition to a systematic trade and economy. This transition brought about rapid changes in the field of trade and commerce transformation as well as in the politico-administrative and economic growth of Goalpara. It was in this period the East India Company had established the salt trade from Bengal to the Brahmaputra Valley of Assam. Goalpara had a well-established trade connection with the Indian subcontinent as well as Southeast Asia and China. Also, rich natural resources and agricultural production are found in this region. Agricultural production has played a significant role both in inland and overseas trade which facilitated the development in trade and economic fields in the Brahmaputra valley during the colonial period.